Totarol as privileged natural product scaffold for antimalarial drug discovery - Gebregziabher, Mengisteab Bereketeab (Department of Chemistry, 2023)
Malaria is one of the major killer diseases in many countries of southern Asia, South America and Africa. Today over 40% of the world population is at risk from malaria. It is the cause of 300 - 500 million infections and the death of more than 2 million people each year, most of whom are African children. Chloroquine has been the mainstream of malaria chemotherapy for nearly 60 years, but widespread resistance now limits its usefulness. A continuous effort to find alternative antimalarials to this drug has led to the discovery of other effective antimalarials of different types, such as aminoquinolines, artemisinins and nucleic acid inhibitors. However, the emergence of multi-drug resistant strains of the malaria parasite has caused a marked increase in malaria related deaths, and there is a continuous need to develop other new antimalarials. Natural products play an important role in the antimalarial drug discovery process. Quinine and derivatives of artemisinin, the two most important drugs available to treat sever falciparwn malaria, owe their origin to plants. Furthermore, several effective antimalarials have been synthesized using quinine as a model compound (e.g., aminoquinoline antimalarials) or are results of relatively simple chemical modifications on the parent natural products (e.g., artemisinin). In this thesis, the natural product scaffold “totarol", which possesses inherent antiplasmodial activity, was used to design and investigate the antiplasmodial activity of three different compound classes namely: Mannich bases, aminoalcohols and semicarbason derivatives. The aim was to incorporate important drug fragments into a natural product scaffold with intrinsic antiplasmodial activity, possibly leading to the discovery of new totarol based antimalarials. In the first class of compounds, a series of novel Mannich base derivatives of totarol have been designed and synthesized to mimic the known Mannich base antimalarials, such as amodiaquine, amopyroquine and other functionally related antimalarials. These compounds differed from each other in the nature of their amino methyl side chain which was varied to include different structural requirements. It was found that the secondary amine Mannich bases possessed better antiplasmodial activity against chloroquine sensitive strains of the parasite than the tertiary amine Mannich bases. However, none of the synthesized compounds were found to be as active as the parent compound (totarol). Based on the preliminary biological evaluations of the synthesized Mannich base derivatives, only selected primary amine derived /f-amino alcohols were synthesized in the second class of antimalarials. However, none of the synthesized compounds were found to possess significant antiplasmodial activity. This was consistent with previous findings whereby the presence of protonatable nitrogen at the beta position could be a necessary structural feature for high antiplasmodial activity with totarol-dcrived amino alcohols. The semicarbazone derivative of totarol also did not show any antiplasmodial activity. Furthermore, none of the 2-isopropylphenol derived Mannich bases showed significant antiplasmodial activity, suggesting the impo1iance of the diterpenoid backbone of totaro, in its inherent antiplasmodial activity.